Technology Corridors in the Production of Commodities and Services - Dan Medovnikov; Stanislav Rozmirovich (Foresight and STI Governance, 2011)
Technology corridors are regarded as a promising new tool for the management of technological development and economic modernization of the economy. The introduction of defined technological corridors can have a significant impact on consumption and lifestyle of a society, so far there is a risk of rejecting the reforms and social tensions.